Visualisation of the network structure in some environmentally degraded natural rubber gloves - Asrul M; Davies R T; Ikram A (Journal of Rubber Research, 2003)
Transmission electron microscopy (TEM) techniques involving swollen rubber samples in a polymerised matrix were used to characterise the network structure of natural rubber glove pieces, which had been degraded in soils and in compost. TEM analysis of changes in the network structure of the rubber latex particles was used together with Fourier Transform Infrared-Attenuated Total Reflectance (FTIR-ATR) spectroscopy to study various stages of degradation. The extent of degradation was visualised as the breakdown of the rubber latex particles into a loose network of chain structures, with the accompaniment of considerable reduction in the number of cis double bonds and the emergence of oxygenated structures. These observations however, could not be related to the actual physical loss in mass of degraded materials, indicating that the degradation process did not occur uniformly on any given piece of material left to decompose.
Keywords: Degradation; Environment; FTIR-ATR; Gloves; Latex particles; Network structure; NR; Transmission electron microscopy